IMPLEMENTATION OF THE CRM SYSTEM AT THE ENTERPRISE - HORDIEIEVA-HERASYMOVA, Liudmyla (Herald of Khmelnytskyi National University. Economic sciences, 2022)
Working with clients is an integral part of the company's activities. In today's world, competition has increased on the market due to an increase in the number of goods and services. As a result, it is more difficult for businesses to find and retain customers. CRM systems make it possible to build relationships with customers more effectively, which helps to improve the level of their service. This makes enterprises more competitive, i.e. gives them some competitive advantages. The result is an increase in the number of customers and an increase in profits, which is the goal of most modern enterprises.Despite the existing benefits of using CRM systems to increase business efficiency, there is still no widespread adoption of such systems in the country. Solving such a problem is possible through comprehensive popularization of such systems for business. It is believed that developers and distributors should become more active in promoting their own product on the market by offering free demo versions, preferential periods for the use of systems, retaining existing customers with offers to reduce fees for use, introducing bonuses, loyalty programs, etc.The market of CRM products in Ukraine is saturated enough for, depending on the industry and tasks, to choose the best option regarding the price and functionality of the purchased system in order to achieve maximum efficiency in managing relations with clientsRegarding the assessment of the effectiveness of the implementation of CRM systems, it is worth applying a statistical method, which can be used to determine the economic effect, taking into account the average positive results of the implementation of information systems at enterprises of a similar industry.CRM systems provide an opportunity to automate not only the process of relations with customers, but also other processes carried out at the enterprise (relationships with personnel, some aspects of management, accounting, control, analysis). This significantly increases labor productivity at the enterprise, allows you to reduce costs and, as a result, increase profits.
Keywords: clients; customer relations; CRM system; effectiveness of implementation